The Effect of Bridge Mass on Violin Frequency Response: An Acoustic and Mathematic Analysis - Lam, Allison (Tufts Archival Research Center, 2020)
My research aims to analyze the relationship between a violin’s bridge mass and itsfrequency response. To investigate this relationship, I used Joseph Curtin’s violin measurement system in conjunction with Chris Rogers’ ObieApp program for testing the frequency response of the violin. In order to verify the accuracy of the measurement system, I performed uncertainty testing. This testing revealed that an uncontrolled hammer tap position leads to the largest margin of error of all measured uncontrolled variables. If we are unable to control hammer tap position, then it can instead be accounted for in the measured margin of error. I then applied this margin of error testing to measurements of frequency response due to different bridge masses. Overall, I found that the intensity of the frequency response decreases as bridge mass increases. However, the specific relationship between frequency response and bridge mass requires further research.To prepare for future research, I created a mathematical model designed to simulate the vibrational behavior of the violin modelled as a rectangular vibrating plate. Though the mathematical model does not exactly replicate a real violin, it provides qualitative similarities to the measured violin frequency response. These similarities include an increase in density of plotted frequencies as frequency increases and a non-monotonic decrease in intensity of plotted frequencies as frequency increases.